Nepalese English (Nenglish): Diverse and expanded assortment of Standard English - Ghimire, Nani Babu (Siddhajyoti Interdisciplinary Journal, 2021)
Nepalese English is a new version of Standard English which is developed due to the effect of the Worlds Englishes. When the English language is expanded, the consequence has been seen in the use of English according to the socio-cultural context of the countries. The use of English either in spoken or written form is also seen differently from the Standard English in Nepal. To uncover this change in the use of English in Nepal, I studied two fictions (novels) written by two Nepalese literary figures in English based on qualitative analysis of the authors’ practice in the use of Nepalese English in writing fiction and found that there is the influence of Nepalese socio-cultural, socio-political, social norms and values in English literature. The finding also illustrated that Nepalese words (characters, location, kinship and taboos terms) are making their entries, complete sentences in Nepali are written, English suffixes are being attached to Nepalese words and vice versa, the word order of English is changed in Nepalese English (Nenglish), the literal translation of Nepalese proverbs are being introduced in English literature. The practice of writing English literature using Nepalese English is being extended to create its own features in English language which leads to develop Nepalese English as a separate variety in the field of language study.